PENGARUH KEPERCAYAAN KONSUMEN PADA MEREK TERHADAP LOYALITAS MEREK PT SINAR MAS WISESA DI BALIKPAPAN - Dewi Ismiyatiningsih (SMART Management Journal, 2021)
This study aimed to test the significance of the influence of consumer trust in the brand to brand loyalty PT Sinar Mas Wisesa in Balikpapan. The model used in this study is SEM (Structural Equation Model) with approach to PLS (Partial Least Square) that is useful to observe the direct and indirect influence of the variables brand reputation, brand competence, quality, trust in the company, brand liking, consumer trust in brand and brand loyalty. This study population are the owners or home buyers in the Balikpapan Baru, the sampling technique used a convenience sampling method in which sampling is done from the customer's most easily found or accessed, the amount of a sample of 128 respondents. The results of this study indicate that the presence of a significant effect of the construct of brand reputation, quality and trust in the company to consumer trust in the brand as well as a significant influence on consumer trust in brand to loyalty brand